PENGARUH KEPEMIMPINAN DAN SISTEM PENGHARGAAN TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI (STUDY KASUS DI PT. PENDIDIKAN GANESHA OPERATION PEMATANGSIANTAR) - Saragih, Roy Sahputra; Siagian, Nancy Florida (Jurnal Ekonomi dan Bisnis (EK&BI), 2018)
The purpose of this study was to determine the effect of leadership and reward systems on Employee Performance with job satisfaction as a mediating variable. With a sample of 70 respondents. The tool used is a questionnaire. The results of this study are that leadership has a positive and significant effect on employee performance. The reward system has significant and significant effect on employee performance, leadership and reward systems have a positive and significant effect on job satisfaction, job satisfaction has a positive and significant effect on employee performance, and leadership, reward systems and job satisfaction has a positive and significant effect on employee performance. With the value of t calculated for leadership variable 2,278 and reward system 3,117 while for job satisfaction as mediation has a value of t count equal to there is a value of 1,994 which means that the value of t count has ?Sig? <0,05. R Square of 0.433, means that variations in employee performance can be explained by variations in leadership, reward systems and job satisfaction by 43.3% and the rest explained by other variations not examined.